Yodha-II: The illustrated military history of India-the crown (1858) to the Kargil war (1999) - Verma, Shiv Kunal (Chandigarh The Browser: JGS Enterprises, 2024)
The military history of Bharat is as panoramic and vast as the Indian subcontinent in which it is rooted. It is epic$1 (Bliterally and figuratively$1 (Bas the Ramayan and the Mahabharat unveil. Few books have attempted to embrace this panorama between their covers, none visually. Yodha: Illustrated Military History of India is the first work to bring this rich military history alive through over Shiv Kunal Verma Illustrated Military History of India The Crown (1858) to The Kargil War (1999) A panoramic book with over 1,600 stunning illustrations, paintings, and photographs covering the majestic canvas of India's military history. 1,600 stunning illustrations, paintings, and photographs. Painstakingly written and put together by the eminent military historian Shiv Kunal Verma, this book covers the period from The Crown (1858) to The Kargil War (1999). This masterly work deserves a place on every bookshelf$1 (Bthat of the student or teacher, soldier or civilian, fauji enthusiast or academic researcher.s
Keywords: Military History of India; Kargil War